O sentido da morte de Jesus de Nazaré - Lopes, Francisco Valter (2011)
The painful and violent death suffered by Jesus was consequence of his prophetic acts, his religious doctrines opposed to the Temple role and to Moses‟ Law and the announcement of the Kingdom. The significance of Jesus of Nazareth‟s death can not be apart from his existence and his mission as Son of God. Jesus of Nazareth surrenders to the Father on behalf of his brothers/sisters and for the reason that will provide them with abundant life. The expression died for us‟ demonstrates that the meaning of Jesus‟ death is understood as a solidary act provided to humanity. This continuous act of Jesus has dictated all his mission, realized in the name of God Father and his Spirit, revealed in his message. His death must be understood as an act of fraternal solidarity, while at the same time, of liberation, for such was a symmetric event with his own life. Jesus has taken to the cross the weight of our sins. In this way of revelation from God, we see his suffering and death not as a failure of a human project, on the contrary, as the Son of God‟s passion which brings salvation. The meaning of Jesus‟s death does not reveal us a cruel God, demanding from his Son an endless sacrifice in order to redeem humanity from its sins and bring it to a free, fulfilling life and in that sense saved. The reflection about the meaning of the death of Jesus of Nazareth implies the perception of the lack of goodness in reality and the desire to correct the human injustices which bring death and lead to the cross. Therefore, Jesus‟ death gives us the possibility to assume our human condition with a glimmer of hope. We have in his death, which wasn‟t for himself, but for us, the strength to preserve the meaning of our existence and to support our encouragement for the reality of the Kingdom, inaugurated by us and definitely sealed with the death on the cross for us and for our salvation